Validations on satellite based potential fishing zone advisories along Goa, south-west coast of India - Sreekanth, G. B.; Subramanian, S.; Manju Lekshmi, N.; Madhu, V. R.; Maria Fernandes, Passta; Singh, N. P. (Indian Journal of Fisheries, 2016)
The annual harvestable marine fisheries potential of Goa is estimated to be about 1.5 lakh t of which 50% is exploited. Potential fishing zone (PFZ) forecasts based on remotely sensed chlorophyll concentration and sea surface temperature are being applied for harvesting marine fishery resources. In this context, a validation study was carried out to analyse the effectiveness of PFZ advisories for Goa coast by 290 simultaneous purse-seine fishing experiments in PFZ and non-PFZ regions. A total of 290 feedbacks were collected from 290 fishing experiments within and outside the PFZ region with similar capacity vessels during 2006-2012. There was 50% reduction in scouting time for the purse-seine fishing which utilised the PFZ advisories. Purse-seiners were benefitted with a significantly higher (p<0.01) mean CPUE (4188.6 kg h-1) and mean profit (`2.72 lakhs) by fishing in PFZ regions in comparison with the mean CPUE (1783.5 kg h-1) and mean profit (`0.86 lakh) of non-PFZ regions. It was observed that the CPUE in purse-seine fishery was improved by 2.3 times by using PFZ advisories. Moreover, the benefit cost ratio significantly (p<0.01) improved in purse-seine fishing from PFZ regions (2.48) compared to non-PFZ regions (0.79). The species-wise analysis showed that Indian mackerel, Indian oilsardine, horse mackerel and seerfish formed the major species that differentiated the catches from PFZ regions. Thus, it was inferred that the PFZ advisories basically holds good for the pelagic species. The use of oceanographic and plankton data for species-specific forecasts in the future is discussed.